Hypothermia for Traumatic Brain Injury in Children—A Phase II Randomized Controlled Trial. Issue 2 (April 2016) - Beca, John; McSharry, Brent; Erickson, Simon; Yung, Michael; Schibler, Andreas; Slater, Anthony; Wilkins, Barry; Singhal, Ash; Williams, Gary; Sherring, Claire; Butt, Warwick
Abstract : Surv Anesthesiol 2016;60(2):73–74 This pilot study was undertaken to test the hypothesis that early and prolonged therapeutic hypothermia (TH; continued for a minimum of 72 hours, with rate of rewarming guided by intracranial pressure [ICP] and cerebral perfusion pressure [CPP]) would improve the outcome in children with traumatic brain injury (TBI). This multicenter trial, conducted in all 8 of the pediatric intensive care units (PICUs) in Australia and New Zealand and 1 in Canada, tested the protocol (including adherence, safety, and outcomes) in order to assess the feasibility of a phase III randomized controlled trial (RCT).